Metabolism of Albumin after Continuous Venovenous Hemofiltration in Patients with Systemic Inflammatory Response Syndrome. (14th January 2015) - Chen, Yu; Ren, Jianan; Qin, Xiaodong; Li, Guanwei; Zhou, Bo; Gu, Guosheng; Hong, Zhiwu; Aa, JiYe; Li, Jieshou
Abstract : Background . The systemic inflammatory response syndrome (SIRS) is characterized by a hypercatabolic state induced by inflammatory mediators. Continuous venovenous hemofiltration (CVVH) stabilizes the internal environment but also aggravates loss of amino acids. The effect of CVVH on protein dynamics is largely unknown. We adopted the stable isotopic tracer technology to investigate how CVVH changed serum albumin metabolism. Methods . Twenty SIRS patients were randomized into low- (2000 mL/h) and high- (4000 mL/h) volume CVVH groups according to the rate of replacement fluid. Eight patients with abdominal infection matched for age, sex, and laboratory index served as controls. Consecutive arterial blood samples were drawn during a primed-constant infusion of two stable isotopes to determine the albumin fractional synthesis rate (FSR) and fractional breakdown rate (FBR). Results . Before treatment, there was no significant difference of FSR and FBR among 3 groups. After CVVH, the albumin FSR in high- and low-volume groups was 7.75 ± 1.08% and 7.30 ± 0.89%, respectively, both higher than in the control (5.83 ± 0.94%). There was no significant difference in albumin FBR after treatment. Conclusions . Protein dynamic indicators could reflect protein synthesis and breakdown state directly and effectively. CVVH increased albumin synthesis, while the breakdown rate remained at a high level independently of the CVVH rate.